Planting seasons and environments in initial field establishment of yerba mate clonal cultivars in Southern Brazil - Saudade de Aguiar, Natália; Moreno Gabira, Mônica; Santin, Delmar; Deschamps, Cicero; Vieira Helm, Cristiane; Wendling, Ivar (Revista Ceres, 2023)
Despite the great economic importance of yerba mate (Ilex paraguariensis A. St.-Hil.), information about clonal plantations and planting conditions of this tree is still scarce. Thus, we evaluated initial field establishment of five clonal yerba mate cultivars, planted at three seasons of the year (summer, autumn, and spring) in a shaded environment, and in the autumn, we also established blocks in a full sunlight environment, to compare both cultivation environments. We evaluated plants at 3, 6, 9, and 12 months after planting, counting the surviving plants, shoots number, and measuring height and canopy diameter. At 12 months we also analyzed the caffeoylquinic acids (CQA) contents in mature leaves from different environments. Plant survival and growth were not affected by planting seasons. Cultivars Aupaba and BRS 409 had the highest survival rates in all seasons evaluated. The shaded environment provided greater survival and growth than full sunlight, also showing higher CQA levels in the leaves. Clonal cultivars Aupaba, BRS 408, and BRS 409 presented higher growth in both environments. The severe drought in the first year may have affected survival; however, growth was considered satisfactory and plants’ initial establishment was better in the shaded environment.